Assistance in Improving English Vocabulary Through the Picture Identification Method for Seventh-Grade - Anis Komariah; Ilham Adha; Rostanti Toba; Dina Destari (Pengabdian Cendekia, 2026)
This community service activity aims to improve students' vocabulary mastery through the implementation of the Picture Identification method as an interactive and contextual learning approach. The implementation method consisted of four stages: needs identification, development of instructional media and tools, implementation of the assistance program, and evaluation through observation of learning activities. The evaluation results show that the application of the Picture Identification method had a positive impact on improving students' vocabulary mastery. The mean score increased from 79.09 on the pre-test to 98.91 on the post-test. In addition, students demonstrated more active participation during learning, greater confidence in pronouncing English vocabulary, and more enthusiasm in following each stage of the assistance program. The Picture Identification method thus proved effective in improving students' English vocabulary mastery while creating a more active, enjoyable, and interactive learning atmosphere at SMP IT Insan Mulia Balikpapan.